Chapter 3 - Complex Reactions: Kinetics and Mechanisms - Ordinary Differential Equations - Graph Theory - Constales, Denis; Yablonsky, Gregory S.; D'Hooge, Dagmar R.; Thybaut, Joris W.; Marin, Guy B.
Kinetic experiments are experiments in which the change of chemical composition of the reacting mixture is monitored in time and/or as a function of the various parameters of the system, in particular the inlet or initial chemical composition, temperature, catalyst state, etc. The main paradigm of contemporary chemical kinetics is the following: a chemical reaction is complex and consists of a set of elementary reactions for which the kinetic laws are assumed to be known.
Keywords: KINETICS; MECHANISMS; COMPLEX REACTIONS; ORDINARY DIFFERENTIAL EQUATIONS; GRAPH THEORY